The Influence of Auditor Type and Financial Performance on Auditor Opinions in Manufacturing Companies - Indrawati, Mos; Abdurrahman, Abdurrahman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The research is directed to find empirical evidence regarding the effect of auditor type and financial performance on WTP audit opinion. Auditor Type is peroxide as Local and No Local Auditor Type. In measuring financial performance, EVA is used. The audit opinion of WTP and non-WTP is a form that represents the opinion of the auditor in this study. Purposive sampling is the method used in determining the sample, with a total of 138 companies. Logistic regression was used in analyzing the data through SPSS 23.0. The conclusion of the study is that the audit opinion of WTP has a significant influence on the type of auditor and the company's financial performance.